Impact of job control, job demand and social support on turnover intention among academics in a Malaysian private university - Ramli, Afdzal Aizat (2013)
In view of the rapid development especially in the global knowledge economy, it is important that in order to sustain and be successful, the higher education institution should retain good and experienced academics. They are regarded as the repository of knowledge, disseminators of knowledge and creators of new knowledge. However, as Malaysia is expected to be a regional hub for international higher education; consequently it can burden the academics particularly in the private institution of higher learning. As such, it triggers stress among the academics and will lead them to stimulate the turnover intention. However, academics turnover intention can be considered as dangerous because it not only have impacts on the institution but also directly and indirectly on the student itself in terms of negative consequences. Therefore, this study attempts to determine the relationship between job demand, job control and social support on turnover intention and also the effects of job control and social support as the moderator in the relationship between job demand and turnover intention. This study draws on the empirical results from 201 academics in private institutions of higher learning in the Klang Valley by using simple random sampling. The hypotheses were tested by using the Pearson Product-Moment Correlation and the hierarchical multiple regression analysis in order to examine the relationship between the three independent variables with turnover intention as well as the moderator effect. Instruments were used from Job Content Questionnaire (Karasek, 1985) and turnover intention from O'Driscoll and Beehr's, (1994). The empirical results support the view that job control determine the level of turnover intention as well as social support on turnover intention. The regression estimation shows that social support was significantly reflected in turnover intention among academics. The findings suggest that if the private institution want to make a better account in sustaining and achieving success in the global knowledge economy; it should place much greater emphasis not only on the role of social support (co-worker and supervisor) but also by providing academics with greater job control in order to retain them. Social support from co-worker and supervisor is viewed as an important element in order to eliminate or buffer the stress which is derived from excessive job demand while job control provides academics with the sense of autonomous in delivering their jobs and role to the institution.